Science for some: examining representations of relevancy and multiculturalism in Texas biology standards and textbooks - Vasquez, Stacy; Atwood, Erin D. (Frontiers in Education, 2023)
Curriculum standards play an important role in the development of instructional materials considering they are used as a framework by publishing companies to outline textbooks. Therefore, it is imperative that standards and instructional materials integrate relevant interdisciplinary content that fosters the development of scientific literacy, health literacy, environmental literacy, and multicultural awareness. This qualitative research critically examines the Texas Essential Knowledge & Skills (TEKS) biology standards and three commonly adopted biology textbooks to determine the degree of relevancy and inclusion of multicultural content using James A. Banks’ Levels of Integration of Multicultural Content. The researchers found that the inclusion of concepts of relevancy and multiculturalism are absent or minimal from the standards and textbooks and conclude that curricular transformation is needed to prioritize and support relevancy and multicultural teaching and learning in biology classrooms. Opportunities to enrich biology standards and textbooks that fall within the transformative approach and social action approach of Banks’ Levels of Integration of Multicultural Content to promote relevancy and multiculturalism are presented.